If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(x) = 4logx Multiply F * x xF = 4logx Solving xF = 4glox Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4glox' to each side of the equation. -4glox + xF = 4glox + -4glox Combine like terms: 4glox + -4glox = 0 -4glox + xF = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(-4glo + F) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-4glo + F)' equal to zero and attempt to solve: Simplifying -4glo + F = 0 Reorder the terms: F + -4glo = 0 Solving F + -4glo = 0 Move all terms containing x to the left, all other terms to the right. Add '-1F' to each side of the equation. F + -1F + -4glo = 0 + -1F Combine like terms: F + -1F = 0 0 + -4glo = 0 + -1F -4glo = 0 + -1F Remove the zero: -4glo = -1F Add '4glo' to each side of the equation. -4glo + 4glo = -1F + 4glo Combine like terms: -4glo + 4glo = 0 0 = -1F + 4glo Simplifying 0 = -1F + 4glo The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| 3485x^2-311107.5x-18855000=0 | | n/36=17/72 | | 7w+6-3w=6 | | 4(2b-5)=2b+10 | | X/5-7=2 | | 2.3=y+.9 | | 12c-48=84 | | 9x-5=3x+47 | | x(x+13)=40 | | (1+2i)*x+(3-5i)*y=1-3i | | -3=2-(-x/5) | | 14x^2-5x+1=0 | | -12+x=60 | | 7x^2-14x-5=0 | | -6/13f=-48 | | 2nw=a | | xy-bx-ay+ab=0 | | 7/x=35/15 | | 2/3=5/2g | | x/12=12/72 | | -5/7d=15/14 | | y=4(27)+3 | | -7y+3=38 | | a+57=-60 | | -9h-6+12h=22 | | -5/24=-13/12-c | | 4(a*2+18)= | | 7x*(3-x)=0 | | F(x)=x^2+14x+46 | | 8y+3-2y=-21 | | 5+ln(27x)=26-2ln(x) | | 7t^2+16t^1-15=0 |